Reasons for limited responses to HIV/AIDS in certain faith-based ministries : a case study of Cloud and Fire Ministery, Kanye, Botswana - Pinto, Joyce Wanjiru (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.